Pelatihan Pijat Tradisional dalam Pengatasan Stunting di Puskesmas 2 Blahbatuh, Gianyar - Anton, Sri Sulistyawati; Dewi, Ni Made Umi Kartika; Diaris, Ni Made; Sinarsih, Ni Ketut; Kartika, I Gusti Agung Ayu; Wiguna, I Nyoman Agus Pradnya; Suputra, I Kadek Darmo; Ariani, Ni Nyoman (Sevanam: Jurnal Pengabdian Masyarakat, 2024)
Stunting is a major health issue affecting children's physical and cognitive development in Indonesia, particularly in Gianyar, Bali. This condition is often caused by inadequate nutrition and chronic infections in early childhood. This community service program aimed to provide training in traditional Balinese massage as a potential intervention to manage stunting. The method involved direct training and demonstration of massage techniques to the parents of 21 children aged 12-60 months with stunting together with their parents. Evaluation was conducted through measurements of height, weight, and other health parameters such as appetite and sleep quality. The results showed that traditional massage techniques effectively increased appetite and improved sleep quality. Approximately 80% of parents mastered the massage techniques and reported positive changes in their children. In conclusion, traditional Balinese massage holds promise as a culturally relevant intervention for stunting management and could be integrated into formal healthcare programs.